2013
DOI: 10.1108/jfmm-03-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Can Islam and status consumption live together in the house of fashion clothing?

Abstract: Purpose -Religion is a significant force in the lives of many people, however; its role in fashion clothing consumption is still unclear. To expand the knowledge on this issue, the present study seeks to understand the role of religiosity in affecting status consumption and fashion consciousness (FC) among Generation Y Muslim consumers, specifically focussing on Iran. Design/methodology/approach -A survey was designed and administered in Iran to a sample of 300 young adults aged between 18 and 24. Findings -Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 74 publications
5
63
1
Order By: Relevance
“…Fashion-conscious consumers would be highly involved with fashion, like to keep abreast of the latest fashion, and place a high importance of the latest fashionable and attractive styling (O'Cass et al 2013). Thus they would tend to seek new fashion items by visiting stores (offline and online) with excitement and pleasure.…”
Section: Website Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Fashion-conscious consumers would be highly involved with fashion, like to keep abreast of the latest fashion, and place a high importance of the latest fashionable and attractive styling (O'Cass et al 2013). Thus they would tend to seek new fashion items by visiting stores (offline and online) with excitement and pleasure.…”
Section: Website Qualitymentioning
confidence: 99%
“…Lertwannawit and Mandhachitara (2012) proposed that people who were fashion conscious tended to have the desire for and adoption of up-to-date styles so that they could maintain their status in their social network. This notion implies that fashion conscious people tended to keep up with the latest fashion, and subsequently, when encountering stimuli, they would be more prone to engage in impulse buying (Leong et al 2018 andO'Cass et al 2013).…”
Section: Reliability and Validity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study of O'Cass, Lee and Siahtiri (2013) revealed that role of religiosity is too strong when it comes to the status consumption and fashion consciousness among Muslim consumers. Identical results were concluded by Siala (2013) when he explored religious influences on consumers' high-involvement purchasing decisions and showed a positive relationship between the exogenous religiosity and religious centrism constructs, and the endogenous attitudinal brand loyalty, price tolerance and word-of-mouth constructs.…”
Section: Religiosity and Its Impact On Behaviormentioning
confidence: 99%
“…There are few age structures based on social and ethnic diversity, buying behaviour or employment [15]. Most papers regarding fashion clothing cover either the entire cohort [16] or specific segments regarding students or tax-payers [17][18][19][20][21]. These studies focused on purchasing motivation, information sources, willingness-to-pay, willingness-to-accept, or eliciting consumer preferences.…”
mentioning
confidence: 99%